Duchenne muscular dystrophy and caregiver burden: a systematic review. (14th June 2018) - Landfeldt, Erik; Edström, Josefin; Buccella, Filippo; Kirschner, Janbernd; Lochmüller, Hanns
Abstract : Aim: To conduct a systematic literature review of caregiver burden in Duchenne muscular dystrophy (DMD). Method: We searched Embase, Web of Science, and PubMed for full‐text articles reporting results from studies of caregiver burden in DMD. Results: We identified 483 unique publications. Of these, 450 were excluded after title and abstract screening, and 12 after full‐text review. A total of 21 articles were included for data synthesis. Results encompassing more than 15 aspects of caregiver burden, investigated through surveys and/or interviews across 15 countries, were identified in the literature. Caregiving in DMD was frequently associated with impaired health‐related quality of life, poor sleep quality, reduced family function, depression, pain, stress, sexual dysfunction, and/or lower self‐esteem, as well as a considerable impact on work life and productivity. Interpretation: Providing informal care to a patient with DMD can be associated with a substantial burden. Yet, more research is needed to better understand the clinical implications of caregiving in DMD and the relationship between caregiver burden and the progression of the disease. Our data synthesis should be helpful in informing clinical and social support programmes directed to families caring for a patient with DMD. What this paper adds: A substantial body of evidence describes caregiver burden in Duchenne muscular dystrophy. Little is known of the family burden beyond caregivers' self‐assessments. What this paper adds: A substantial body of evidence describes caregiver burden in Duchenne muscular dystrophy. Little is known of the family burden beyond caregivers' self‐assessments. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.